1986
DOI: 10.1017/s0021859600061840
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on the response of maize to K fertilizer in the tropics

Abstract: SUMMARYA study designed to investigate the effect of K nutrition on the yield, components of yield and on macro- and micronutrient concentration of maize showed no significant effect of K on yield in forest alfisols derived from basement complex rocks and in savannah alfisols derived from sandstones in the tropics. Potassium addition significantly decreased lodging, but had little influence on cob length, ear weight, shelling percentage or moisture content.Ear-leaf N and K were significantly increased, while C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
0
0
1
Order By: Relevance
“…The significant increase in leaf N with K application noticed in this study has been reported in maize in this region (Kayode, 1986), while the higher P in the seed than the leaf or shell has already been documented (Hallock et al 1971;Gopalakrishnan & Veerannah, 1968;Puntamkar & Bathkal, 1967;Millar, 1955). The significant increase in leaf K is in accordance with an earlier study (Gillier & Gautreau, 1971) while the highest K concentration reported in the leaf agrees with Gopalakrishnan & Veerannah (1968) and Puntamkar & Bathkal (1967).…”
Section: Discussionsupporting
confidence: 76%
“…The significant increase in leaf N with K application noticed in this study has been reported in maize in this region (Kayode, 1986), while the higher P in the seed than the leaf or shell has already been documented (Hallock et al 1971;Gopalakrishnan & Veerannah, 1968;Puntamkar & Bathkal, 1967;Millar, 1955). The significant increase in leaf K is in accordance with an earlier study (Gillier & Gautreau, 1971) while the highest K concentration reported in the leaf agrees with Gopalakrishnan & Veerannah (1968) and Puntamkar & Bathkal (1967).…”
Section: Discussionsupporting
confidence: 76%
“…En el caso de este catión, 58% de los sitios analizados se ubicaron en la categoría de deficientes con valores menores a 5% de saturación. Diversos estudios han demostrado que el K es un elemento importante para incrementar el rendimiento de grano y reducir el acame del tallo del maíz, su deficiencia influye en la magnitud de la tasa fotosintética y la senescencia prematura de las plantas (Smith y White, 1988), así como en el deterioro progresivo de los tres nudos basales del tallo del maíz, y el consecuente acame de la planta (Liebhardth y Murdock, 1965;Kayode, 1986).…”
Section: Clase De Suelounclassified